Effects of commercial freshwater bathing on reinfection of Atlantic salmon, Salmo salar, with Amoebic Gill Disease - Clark, GA; Powell, MD; Barbara Nowak (2003)
Fish with Amoebic Gill Disease (AGD) were examined over a 10-day period following commercial freshwater bathing to assess the time to reinfection. Samples were taken from fish before freshwater bathing and then 1, 3, 5 and 10 days after bathing to determine the number of amoebae present on the gills. Freshwater bathing significantly reduced the number of amoebae on the gills, with an 86 Â± 9.1% reduction in the number of live amoebae found on the gills after freshwater bathing. However, amoeba numbers returned to pre-bath levels 10 days after bathing. There was no significant effect on number of AGD lesions/filament, the mean ranged from 0.08, 3 days after bathing, to 0.14, 5 days after bathing. However, the number of Neoparamoeba pemaquidensis dramatically dropped in histological sections from 0.53 per AGD lesion before the bath to 0 per AGD lesion 1 day after the bath and then remained significantly lower, reaching 0.08 per AGD lesion 10 days after the bath. The number of mucous cells changed, with Alcian blue (AB) (pH 1) positive cells decreasing immediately after bathing. Results of this study show that commercial freshwater bathing is effective at removing amoebae from the gills of fish, however, reinfection can occur within a week. Â© 2003 Elsevier Science B.V. All rights reserved.